Organization of international cooperation on the university level - Kowalski, Paweł (НТУ "ХПІ", 2015)
The article analyzes the problems of international cooperation of universities in the context of history and modernity of their development. The article provides an analysis of the impact of university's international relations towards the quality of its education. In the article thetre is considered the history of formation of Taras Shevchenko National University of Kyiv, as well as its role in the development of higher education in Ukraine. The advantages of international education and its possibilities in development of national higher education systems and discussed the content of the classical model of international cooperation. In addition, the article contains conclusions and generalizations to pass into consideration not only the experience of international universities, including the national traditions and culture of a particular people in building their own system of higher education.

У статті аналізуються проблеми міжнародного співробітництва університетів у контексті історії та сучасності їх розвитку. У статті наведено аналіз впливу університету міжнародних відносин до якості своєї освіти. У статті розглядається історія становлення театру імені Тараса Шевченка Київський національний університет, а також її роль у розвитку вищої освіти в Україні. Переваги міжнародної освіти та її можливості в розвитку національних систем вищої освіти та обговорили зміст класичної моделі міжнародного співробітництва. Крім того, стаття містить вис-новки та узагальнення проходити до уваги не тільки досвід міжнародних університетів, у тому числі національних традицій і культури того або іншого народу в побудові своєї системи вищої освіти.
Організація міжнародного співробітництва на університетському рівні
Keywords: efficiency; benefits; international education; classical model; student mobility; ефективність; перевага; модель класична; мобільність студентська; управління